2020
DOI: 10.1007/s10803-020-04526-z
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Autism Symptom Severity Change During Early Childhood

Abstract: Autism symptom severity change was evaluated during early childhood in 125 children diagnosed with autism spectrum disorder (ASD). Children were assessed at approximately 3 and 6 years of age for autism symptom severity, IQ and adaptive functioning. Each child was assigned a change score, representing the difference between ADOS Calibrated Severity Scores (CSS) at the two ages. A Decreased Severity Group (28.8%) decreased by 2 or more points; a Stable Severity Group (54.4%) changed by 1 point or less; and an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 84 publications
(96 reference statements)
3
56
0
5
Order By: Relevance
“…Of the studies that reported participants' IQ metrics, all mean FSIQ and VIQ scores were within the average to above average range of intelligence. A minority of studies included in the current review included autistic participants with higher support needs, and/or lower verbal or intellectual ability (Damico & Nelson, 2005;Frith, Happe, Siddons, Happé, & Siddons, 1994;Livingston et al, 2018;Sutherland, Hodge, Bruck, Costley, & Klieve, 2017;Waizbard-Bartov et al, 2020). These findings are consistent with recent evidence showing a selection bias skewed toward inclusion of more cognitively able research participants across ASD research, a trend which has been increasing in specific domains of ASD research in recent years (Stedman, Taylor, Erard, Peura, & Siegel, 2018).…”
Section: Participant Characteristicssupporting
confidence: 84%
“…Of the studies that reported participants' IQ metrics, all mean FSIQ and VIQ scores were within the average to above average range of intelligence. A minority of studies included in the current review included autistic participants with higher support needs, and/or lower verbal or intellectual ability (Damico & Nelson, 2005;Frith, Happe, Siddons, Happé, & Siddons, 1994;Livingston et al, 2018;Sutherland, Hodge, Bruck, Costley, & Klieve, 2017;Waizbard-Bartov et al, 2020). These findings are consistent with recent evidence showing a selection bias skewed toward inclusion of more cognitively able research participants across ASD research, a trend which has been increasing in specific domains of ASD research in recent years (Stedman, Taylor, Erard, Peura, & Siegel, 2018).…”
Section: Participant Characteristicssupporting
confidence: 84%
“…It is also important to investigate the stability of these sensory phenotypes over time, as the current study identified age differences across the sensory phenotypes. Further, given the utility of clustering techniques for parsing the heterogeneity in traits and behaviours that has already been demonstrated [ 63 65 ], future work should apply these clustering techniques to traits such as anxiety, restricted and repetitive behaviours, and social communication difficulties to determine whether discrete phenotypes can also be identified. In addition, while these sensory phenotypes were related to current behavioural differences, future work should aim to determine whether these phenotypes are also predictive of future behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the average age of diagnosis in the United States remains around 4 years of age [Christensen et al, 2016]. While there is mixed evidence for the stability of autism traits over early childhood [Bieleninik et al, 2017; Waizbard‐Bartov et al, 2020], the delay in diagnosis can still impact timely intervention during a critical window of development. In response to this, in 2007 the American Academy of Pediatrics published guidelines supporting the need for all children to be screened for ASD between 18‐ and 24‐months of age as part of their well‐child visits [Myers, Johnson, & Council on Children With Disabilities, 2007].…”
Section: Introductionmentioning
confidence: 99%